Determinação de elementos terras raras em amostras ambientais por cromatografia líquida de alta eficiência com pareamento iônico - Colim, Alexsandro Nunes (2018)
Rare earth elements (ETRs) comprise a group of 17 chemical elements formed by the series of lanthanides, from lanthanum (La) to lutetium (Lu), added to scandium (Sc) and yttrium (Y) elements. Currently they are widely used in the manufacture of high technology products such as LED televisions, smartphones, electric vehicles as well as clean energy generation (wind and solar). Lately, ETR production is concentrated in China, controlling the global supply of the raw material. Currently, Brazil (and other countries) is seeking the resumption of the acquisition processes and the search for new mining areas of ETR. In the present work, the city of Lavras do Sul is investigated as a possible zone of obtaining ETR, being considered one of the regions with the highest concentration of minerals in the state of Rio Grande do Sul. For this purpouse a chromatographic method was developed and validated in terms of the main analytical characteristics for the determination of 15 rare earth elements (La to Lu and Y) using high-performance liquid chromatography with ion-pairing and post-column derivatization in water and soil samples. The calculated values of the instrumental detection limits ranged from 0.023 to 0.158 μg mL-1, for the most sensitive analyte (Dy) at least sensitive (La), respectively. Similarly, the calculated values of the instrumental quantification limits ranged from 0.069 μg mL-1 (Dy) to 0.480 μg mL-1 (La). Intra-day precision presented relative standard deviation values ranging from 0.22% (Ho) to 4.08% (La) and, inter-day, ranging from 1.07% (Yb) to 4.86% (La). During the evaluation of the selectivity of the method, it was found that Ni, Cu, Zn and Pb caused interferences in the determination of the ETR, since they formed absorbing complexes with the PAR complexing agent (used in post-column derivatization) and had retention times similar to those of the analytes. In this way, procedures for the removal of interferents were investigated. For the determination of ETR in samples (natural and artificial) of water, a procedure using ion exchange mini-columns proved to be efficient. Metal ions in solution were previously adsorbed on strongly acid cationic resin. Interferences were initially eluted with 15 mL of HCl (1 mol L-1). The ETRs were removed from the column, as a single set, with 13 mL of HNO3 (6 mol L-1, 50 ⁰C). For the determination of ETR in natural soil samples, a procedure by fractional precipitation was applied. After the mineralization of the samples (1.0 g of mass with 10 mL of concentrated HNO3 in a heated block at 90 ± 5 ⁰C for 72 hours with a final volume of 40 mL by the addition of ultrapure water), the interfering elements were separated from the ETR by precipitation of their respective insoluble hydroxides, through successive adjustments of the pH value of the sample (with NH4OH). The insoluble hydroxides of the ETR were obtained in pH values from 6.0 to 8.5. After centrifugation and filtration steps, the precipitates containing the ETR were redissolved in HNO3 (2 mL, 2 mol L-1) and were thus free of interferents. Under these conditions a 20-fold preconcentration factor was achieved. The results determined in the water and soil samples were compared with a reference method (ICP-MS), demonstrating that the proposed chromatographic method generates reliable results for the determination of the 15 ETRs (La a Lu and Y).